Financial Innovation as an Entrance to Sustainable Financing A Case Study of Islamic Banks in the State of Qatar (2014-2018) - جمال, ابراهيم حسن (Journal of Economics and Administrative Sciences, 2020)
While the impact of the fourth Industrial Revolution on the economy keeps accelerating, the signs of the fifth industrial revolution, whose key is innovation and creativity started to evolve. However, the challenge of achieving sustainable development and its goals remains faced by the global organizations; In this situation, Islamic banks are exposed to many challenges among which is the challenge of keeping themselves abreast of the latest developments in the modern technology which in turn is a tool for continuity and competition. On the flip side, to avoid the negative impact that these changes can have such as an increased gap between financial innovations and the requirements of sustainable development. Islamic banks in their nature are considered more demanded to fulfill these requirements than their counterparts. Thus, this study comes as an attempt to adopt some guidelines on how to take advantage of the challenging financial innovation to address challenging sustainability by introducing innovating sustainable finance products in Islamic banks. The study aims at illustrating the concept of financial innovation and sustainability, and to shed light on the importance of financial innovation to the Islamic finance industry. Also, the study examines the status quo of the Islamic banks in the State of Qatar by highlighting their practices related to sustainability and products thereof. Finally, the study proposes some general guidelines for innovative and sustainable financing models. The descriptive method was used in the study with an analytical method in some areas.  The study concludes with a number of results and recommendations, among which are financial innovation is critically important within Islamic financial institutions, the existence of a distinguished catalytic regulatory environment in Qatar to achieve the Sustainable Development Goals, more attention is needed to the development of Islamic finance products in line with the legal objectives which support sustainability requirements as well.